The Assessment of Physical Fitness and Morphofunctional State of Female First-Year Students in Non-Linguistic Higher Education Institutions - Svitlana Solohubova; Olena Lakhno; Volodymyr Shyyan; Olga Shyyan (OVS LLC, 2020)
The purpose of this research paper is to study physical fitness and functional state of female first-year students in Prydniprovska State Academy of Civil Engineering and Architecture. Materials and methods. The study involved 100 female first-year students of general group aged 17-18, all after medical examination and obtaining doctor's approval: the age group was 18 years old (n = 100). To meet the goals set, the following research methods were used: theoretical analysis and generalization of data in specialized scientific and methodological literature, pedagogical testing, anthropometric research methods, functional methods of cardiorespiratory system investigation and methods of mathematical statistics for processing the results of the research. Results. the conducted study proved the hypothesis on the necessity to improve the system of physical education in technical higher educational institutions, which is connected with the low level of physical fitness among students. Conclusions. The study revealed the low level of physical fitness among the investigated students in terms of speed and strength endurance indicators (with 83%), explosive physical force of the lower limbs (with 82%) and strength endurance of the upper limbs (with 68%), as well as reduced functional characteristics: resistance to hypoxia (according to the results of the Shtange test with 46% and the Gench test with 49%), workability (with 71%) and efficiency of cardiovascular system (with 55%). Low physical fitness levels among the tested girls necessitate the additional introduction of more intensive training. The high variability of the physical fitness indicators among the students requires personalization of the training process, as well as the obligatory use of express testing methods for the physical state of each student during a workout.